Pengaruh Pengelolaan Keuangan, Kepatuhan Akuntansi dan Pengawasan Internal Terhadap Kualitas Laporan Keuangan Bumdes Teluk Mengkudu - Muhammad Handika; Mas'ut Mas'ut; Henny Triastuti Kurnia Ningsih (Universitas Islam Islam Sumatera Utara, 2026)
Village-Owned Enterprises (BUMDes) are essential pillars for enhancing the village economy and public welfare. Good financial management, compliance with accounting standards, and effective internal control are highly required to generate quality financial statements. However, various problems still persist, such as disorderly recording, low compliance with SAK ETAP, and weak internal control systems, which cause the quality of financial statements to be sub-optimal. This research was conducted in Teluk Mengkudu District, Serdang Bedagai Regency, with a total sample of 30 respondents selected using the saturated sampling technique. The data analysis technique used was multiple linear regression analysis, which includes data quality tests, classic assumption tests, coefficient of determination tests, and hypothesis testing. The results of the research indicate that financial management has a positive and significant effect on the quality of financial statements. Accounting compliance also has a positive and significant effect on the quality of financial statements. In addition, internal control has a positive and significant effect on the quality of financial statements. Simultaneously, financial management, accounting compliance, and internal control have a significant effect on the quality of BUMDes financial statements in Teluk Mengkudu District.